Fitness costs of rifampicin resistance in Mycobacterium tuberculosis are amplified under conditions of nutrient starvation and compensated by mutation in the β′ subunit of RNA polymerase. Issue 6 (26th February 2014) - Song, Taeksun; Park, Yumi; Shamputa, Isdore Chola; Seo, Sunghwa; Lee, Sun Young; Jeon, Han‐Seung; Choi, Hongjo; Lee, Myungsun; Glynne, Richard J.; Barnes, S. Whitney; Walker, John R.; Batalov, Serge; et al.
Summary Rifampicin resistance, a defining attribute of multidrug‐resistant tuberculosis, is conferred by mutations in the β subunit of RNA polymerase. Sequencing of rifampicin‐resistant (RIF‐R) clinical isolates of Mycobacterium tuberculosis revealed, in addition to RIF‐R mutations, enrichment of potential compensatory mutations around the double‐psi β‐barrel domain of the β′ subunit comprising the catalytic site and the exit tunnel for newly synthesized RNA. Sequential introduction of the resistance allele followed by the compensatory allele in isogenic Mycobacterium smegmatis showed that these mutations respectively caused and compensated a starvation enhanced growth defect by altering RNA polymerase activity. While specific combinations of resistance and compensatory alleles converged in divergent lineages, other combinations recurred among related isolates suggesting transmission of compensated RIF‐R strains. These findings suggest nutrient poor growth conditions impose larger selective pressure on RIF‐R organisms that results in the selection of compensatory mutations in a domain involved in catalysis and starvation control of RNA polymerase transcription.